Cornelia N. Moore y Lucy Lower (comp.) Translation East and West: A Cross-Cultural Approach; Selected Conference Papers. Hawaii: University of Hawaii Press, 1992, XXV + 257 pp. - Russell Maeth Ch. (El Colegio de México, A.C., 1993)
-